A wide band gap polymer based on indacenodithieno[3, 2-b]thiophene for high-performance bulk heterojunction polymer solar cells. Issue 2 (8th December 2016) - Lee, Woosung; Jung, Jae Woong
Abstract : A novel wide band gap polymer (PIDTT-TT) has been synthesized to use in efficient polymer solar cells with power conversion efficiencies up to 7.10%. Abstract : Although wide band gap polymers have attracted much interest for applications in polymer solar cells (PSCs) as short-wavelength light absorbers in tandem devices, the power conversion efficiencies (PCEs) of wide band gap polymer-based single cell devices are inferior to those of narrow-band gap polymers due to their restricted light absorption range. Thus, it is necessary to develop new semiconducting polymers for optimal device performance. Herein, a new wide band gap polymer (PIDTT-TT) was designed and synthesized by copolymerizing indacenodithieno[3, 2- b ]thiophene (IDTT) with thieno[3, 2- b ]thiophene (TT), resulting in a wide band gap polymer (PIDTT-TT) with an absorption onset at ∼580 nm (optical band gap = 2.14 eV). Electrochemical investigations indicated the low-lying energy levels (HOMO = −5.35 eV) of PIDTT-TT compared to those of P3HT (HOMO = 5.00 eV), which is beneficial for obtaining a high open-circuit voltage ( V OC ) in the device. The optimized morphology of the PIDTT-TT:PC71 BM blend film led to a high V OC (0.96 V) and fill factor (FF) (0.66), which compensate for the limited light absorption range, achieving a power conversion efficiency (PCE) of 7.10%. Furthermore, the deep energy levels of PIDTT-TT reinforced the air stability of the solar cell, which retained 85% of its initial PCE after being stored for 120 h under ambient conditions. Accordingly, PIDTT-TT is a potential candidate for applications in tandem solar cells. This study enriched the design rules of wide band gap polymers for high-performance PSCs.